Evaluation of morphine‐like effects of the mixed mu/delta agonist morphine‐6‐O‐sulfate in rats: Drug discrimination and physical dependence. Issue 4 (19th June 2018) - Yadlapalli, Jai Shankar K.; Bommagani, Shoban Babu; Mahelona, Ryan D.; Wan, Anqi; Gannon, Brenda M.; Penthala, Narsimha R.; Dobretsov, Maxim; Crooks, Peter A.; Fantegrossi, William E.
Abstract: Morphine‐6‐O‐sulfate (M6S) is as a mixed‐action mu/delta (μ/δ) opioid receptor agonist with high potency and analgesic efficacy. These studies used assays of drug discrimination and schedule‐controlled responding to assess abuse‐liability, tolerance, and physical dependence as compared to morphine in rats. Attempts to train 0.3 mg/kg (IP) M6S from saline failed, but all rats rapidly acquired the discrimination when the training dose was changed to 3.0 mg/kg morphine, and substitution tests showed that morphine and fentanyl both fully substituted for the training dose, M6S and M3A6S (3‐O‐acetyl ester of M6S) only partially substituted, and salvinorin A did not elicit morphine‐like effects. Tolerance to response rate‐decreasing effects was studied in rats administered either 1.0 or 3.0 mg/kg morphine or M6S before food‐reinforced operant sessions. At both unit doses, tolerance to M6S‐elicited rate suppression developed more slowly than tolerance to morphine‐induced reductions in response rates. To assess dependence, rats were maintained on 1.0 mg/kg morphine or 1.0 mg/kg M6S until food‐reinforced response rates were stable for at least 5 days. Rats were then administered saline or increasing doses of the opioid antagonist naltrexone (NTX) (0.3, 1.0, 3.0, or 10.0 mg/kg) in order to determine antagonist‐precipitated withdrawal. NTX precipitated withdrawal was similar in both morphine‐maintained and M6S‐maintained rats. In conclusion, the mixed μ/δ agonist activity of M6S failed to completely protect against the development of physical dependence, but delayed tolerance development to behavioral effects and resulted in decreased morphine‐like subjective effects, perhaps implying a decreased abuse liability over μ agonists.